Energy Storage Technologies for Smart Grid: A Comprehensive Review - Surender Reddy Salkuti (Majlesi Journal of Electrical Engineering)
In the recent days, the main challenge for the electrical power system is an economical storage technology. Energy storage is essential for the future Smart Grid (SG) to smooth out the fluctuating output of Renewable Energy Resources (RERs). Even though many good storage technologies are available but either they are not economical or they are not efficient. Several research studies are analyzed the application of energy storage with respect to voltage support, peak shaving, frequency stability, renewable firming, transmission upgrade deferral, and a host of other uses. RERs are dependent on the climate conditions for the power output. Therefore, an efficient storage technology is an important part for the reliability of electric power system. This paper compares different storage technologies available, i.e. hydrogen storage, batteries, superconducting magnet energy storage, fly wheels, compressed air energy storage, pumped hydro energy storage, etc. This paper details the necessity of storage techniques to help the RERs power output in the SG to meet the energy demands of the future.